Celebrate Suffrage - Jung, Patricia Beattie (Journal of the Society of Christian Ethics, 2020)
2020 marks 100 years of women’s suffrage in the U.S. Considering this anniversary and the Christian presumption in favor of democracy, this essay invites readers to honor all those who worked for women’s suffrage in two specific ways. First, it invites them to tell the whole truth about the movement, both its many moments of grace and its moral failures. Second, it encourages readers to make the connection between this ambiguous legacy and ongoing forms of voter suppression in the U.S. and then to celebrate suffrage by finishing the fight for it.